Assessment of Heavy Metal Contamination in Water Resources of the Andean Mining Zone: A Decadal Analysis of the Santa Rosa River Basin, Ecuador - Cobos , Angélica Geovanna Zea; Caballero, Pablo (Journal of Ecohumanism, 2025)
The vast majority of mineral deposits that exist in Ecuador are located in the Andean zone. It is important to carry out permanent monitoring of heavy metals present mainly in the water, especially in regions where mining is one of the economic activities. The objective of this work is to evaluate the possible contamination of the water that supplies the community and that uses it for human consumption, due to the mining activity by potentially toxic elements: Mercury, Arsenic, Lead and Cadmium, and its comparison. with the analyzes carried out in the last 10 years in this same sector of the Santa Rosa river basin, The analysis of the samples was carried out by Atomic Emission Spectroscopy with Inductively Coupled Plasma (ICP-AES), the results obtained show contamination of the water resource, according to the United States Environmental Protection Agency (EPA), and the World Health Organization (WHO) , and from the surveys applied to the community, the use of this water in different activities, both domestic and agricultural, is evidenced, with this a better perspective of the influence of anthropogenic activity on the influence of water quality can be obtained.